Passion for Patriakarlisme: Modstanden mod landboreformerne 1786-1790 - Jensen, Nils Valdersdorf (Temp - tidsskrift for historie, 2014)
Passion for patriarchalism: opposition against agrarian reforms 1786-1790 The matter in question for this article is the resistance towards the reforms of peasant adscription and probate law in the years from 1786 to 1790. In the debate concerning the abolition of peasant adscription the proprietors are reluctant to grant the peasants full freedom. Instead they argue that the emancipation will be detrimental to the nation’s wealth and the military’s strength. The proprietors do not attack the ideal of freedom rather they focus on the practical consequences of emancipation instead. In regards to the reform of probate law the responses are strikingly unanimous. All the proprietors resist the proposal to remove probate authority from the proprietors. In the process of doing so, they all build their arguments upon patriarchal values and a paternalistic view on the peasant class. The article’s analysis of their concept of freedom showcases an absolutist concept of freedom closely intertwined with the patriarchal society. The results show that underneath the Enlightenment runs a strong stream of traditional values – a passion for patriarchalism - that needs to be accounted for when examining this period. The results testify that a dichotomy between modern and traditional thinking doesn’t match the historical reality. The proprietors themselves are a good example of the nuances between the black and white, and their struggle needs to be reviewed.